Efficacy of Rhizobacteria of cabbage against Black Rot of cabbage in Meghalaya - Sudharshan K. R.; Dutta, Pranab (Umiam : CPGS-AS, CAU, 2024)
Black rot of cabbage, caused by gram negative bacterium Xanthomonas campestris pv. campestris (Xcc), affecting cruciferous crops and is a leading cause of substantial agricultural losses on a global scale. The current study focuses on the isolation of antagonist rhizobacteria against black rot of cabbage and aims to provide a safer and more effective biocontrol management of Xcc. Survey was conducted across six districts of Meghalaya for incidence and severity of the disease, showed significantly highest disease occurrence (67.90%) in East Khasi Hills (EKH) district with peak Disease Index (DI) and Per cent Disease Index (PDI) during the monsoon season (2022), correlating with high rainfall (12.86 mm), elevated temperature (21.24°C), and relative humidity (89.20%). Significant correlations were observed between black rot incidence, severity and environmental factors, including temperature (correlation coefficient: 0.91), relative humidity (correlation coefficient: 0.87), and rainfall (correlation coefficient: 0.88). The DI values varied among crucifer crops, and cabbage exhibited the highest DI with 69.98%, while mustard had the lowest DI (26.81%). In terms of PDI in EKH, cabbage with 43.38%, followed by knolkhol at 15.23%, while mustard with lowest PDI (13.72%). The pathogen causing black rot from six crucifer crops, was confirmed through pathogenicity tests and DNA amplification of the hrp F gene as Xcc. Cross-pathogenicity and aggressiveness assays showed highest PDI (61.08%) for the cauliflower isolate XC CALI1. But the highest AUPDC (353.10%) was recorded for broccoli isolate XC BRO1. During the present study 270 rhizobacterial, isolates were isolated. Amongst which, isolates, RE9, SMR8, MST9, NIL3, J8 and LM3 showed significant inhibitory effects against Xcc in agar well assays producing zones against six different black rot strains of crucifer s crop (cabbage, broccoli, cauliflower, mustard, knol khol, and radish). RE9 showed the highest inhibition zone against C CALI1 (2.58 cm), NIL3 exhibited the highest inhibition zone against XC BRO1 (2.77 cm), XC CAB4 (4.08 cm), XC KNKH1 (2.54 cm) and XC MSD2 (3.12 cm), while MST9 showed the highest inhibition zone (3.16 cm) against radish isolates. However, Nil3 and RE9 were the most efficient isolates amongst all. While studying the plant growth promotion activities for 6 potential isolates, RE9 and MST9 showed enhanced seedling development across different crucifer crops. Hydrolytic enzyme assays indicated that these isolates possessed positive response for protease, alpha-amylase, and lipase activities. Furthermore, these rhizobacterial isolates showed antimicrobial activity through siderophore production. Rhizobacterial isolate, NIL3 identified as the most effective isolate for inducing secondary and defense-related metabolites. Gas Chromatography-Mass Spectrometry (GCMS) analysis showed presence of different volatile organic compounds in the isolates, such as Trichloroacetic acid, undecyl ester, Methenamine, and Hexadecanoic acid. Pot and field experiments were conducted to study the efficacy of the potential isolates againt Xcc causing black rot of cabbage. In pot experiment, lowest PDI (21.1%) was found when rhizobacterial isolate NIL3 was used for seedling root dip treatment and two foliar sprays with highest percent disease reduction (70.83%) over control. But the seedling root dip treatment and foliar sprays of RE9 exhibited superior traits in head formation, maturation, plant height, head weight, circumference, and compactness of cabbage. In field experiment combine application of rhizobacterial isolates NIL+RE9+MST9 as seedling root dip along with foliar sprays showed lowest PDI of 18.3% and 22.11% in both summer and winter season (2022- 2023) respectively with the highest per cent disease reduction (79.9% in winter, 75.62% in summer) with higher plant growth and yield attributes. The study provides comprehensive insights into the dynamics of black rot in crucifer crops, highlighting environmental correlations, pathogenic isolates, and the potential of rhizobacterial treatments in disease management and plant growth promotion.
Includes bibliographic references.
Keywords: Cabbage -- Black rot -- Disease